DEVELOPMENT AND APPLICATION OF RAPID XTREME CHAIN REACTION AND LOOP-MEDIATED ISOTHERMAL AMPLIFICATION ASSAYS FOR THE DETECTION OF LEUKAEMIA AND BRUCELLOSIS OF CATTLE - Amenov , A.A.; Kalendar , R.N.; Abeldenov , S.K.; Musakhmetov , A.S.; Li , P.K.; Kiribayeva , A.K. (Eurasian Journal of Applied Biotechnology, 2017)
Infection of cattle with bovine leukaemia virus (BLV) and Brucella spp. result in economic losses due to reduced productivity, reduced milk production, and early culling. Furthermore, BLV and Brucella spp. can potentially infect humans. This study was conducted to develop Xtreme chain reaction (XCR) and loop-mediated isothermal amplification (LAMP) assays for the rapid and efficient detection of leukaemia and Brucella spp. pathogen infections in cattle. Brucella spp. XCR and LAMP assays targeted the host specific antigen gene and IS711 repeats from the transposase gene. To detect BLV proviral DNA, the BLV long terminal repeat region and the Env gene were used to develop XCR and LAMP assays. The results of LAMP assays applied to field samples were compared with those of XCR/LAMP and serological tests for BLV and Brucella spp. The results of the XCR and LAMP assays showed a high level of agreement with those of serological methods, and accurately detected the target sequences with no cross-reactions observed. Therefore, the XCR and LAMP assays described here are highly sensitive and specific tests to detect and differentiate between BLV and Brucella spp. and could help with the detection of infection in the early stages.